News and Analysis : LIGO begins third run. (4th June 2019) - Unknown
Abstract: The US-based Laser Interferometer Gravitational-Wave Observatory (LIGO) based in Hanford, Washington and Livingston, Louisiana, began its third observing run on 1 April.